PEMBERIAN EDUKASI MENJAGA KESEHATAN GIGI DAN MULUT PADA SISWA SD HANG TUAH 6 SURABAYA: PROVIDING EDUCATION ON MAINTAINING DENTAL AND ORAL HEALTH TO STUDENTS OF HANG TUAH 6 ELEMENTARY SCHOOL SURABAYA - Indarti, Cacilia; Izzud, Tandy; Paramita, Annisa Listya; Iman, Dimas; Parwati sari, Rima; Sarianoferni; Sularsih (Universitas Hang Tuah Surabaya, 2025)
Oral health is an important aspect in children's growth and development. Problems such as cavities and poor oral hygiene can affect academic achievement and quality of life. This activity aims to increase student awareness of the importance of maintaining oral health from an early age. This community service was carried out on 83 students in grades 4 and 5 of Elementry School Hang Tuah 6 Surabaya by providing health promotion education and dental and oral examinations. The activity was carried out by involving a team of dentists and assisted by students from the Faculty of Dentistry, Hang Tuah University. It began with a pre-test assessment before education was given and a post-test after education was given, followed by a dental and oral health examination. The average pre-test score was 69.39 and the average post-test score was 86.59. The results of the Wilcoxon Signed-Rank Test, p-value <0.05, showed a significant difference between the Pre-Test and Post-Test scores. This means that after dental health education, their knowledge and awareness of dental and oral health increased. For students who have dental problems such as cavities, they are followed up with dental care at Nala Husada Dental Hospital. It is hoped that with this program, awareness of dental and oral health will increase, the number of cases of toothache and swollen gums will decrease, and there will be changes in behavior in maintaining dental and oral health.